Main Applications and Recent Research Progresses of Additive Manufacturing in Dentistry. (24th February 2022) - Huang, Gan; Wu, Libo; Hu, Jie; Zhou, Xiongming; He, Fei; Wan, Li; Pan, Shu-Ting
Abstract : In recent ten years, with the fast development of digital and engineering manufacturing technology, additive manufacturing has already been more and more widely used in the field of dentistry, from the first personalized surgical guides to the latest personalized restoration crowns and root implants. In particular, the bioprinting of teeth and tissue is of great potential to realize organ regeneration and finally improve the life quality. In this review paper, we firstly presented the workflow of additive manufacturing technology. Then, we summarized the main applications and recent research progresses of additive manufacturing in dentistry. Lastly, we sketched out some challenges and future directions of additive manufacturing technology in dentistry.